Aortic rupture during stenting for recurrent aortic coarctation in an adult: live-saving, emergency, NuDEL all-in-one covered stent implantation. (6th March 2017) - Eicken, Andreas; Georgiev, Stanimir; Ewert, Peter
Abstract: We report a case of successful, life-saving implantation of a covered Cheatham Platinum stent, an all-in-one NuDEL catheter system, in an adult with aortic rupture after bare-metal stenting for re-coarctation of the aorta.